(untitled) (Estima – Brazilian Journal of Enterostomal Therapy, 2021)
Objective: discuss the approach of themes related to stomatherapy in Pedagogical Projects (PP) and syllabuses of undergraduate nursing courses from public institutions of higher education (PIHE) in the Brazilian Midwest. Method: documentary research, exploratory, with a qualitative approach, developed from March to June 2020. The nursing courses were located through access to the Ministry of Education’s online portal (e-MEC) and the PP and the subject syllabuss were accessed, when available. Results: The sample consisted of 17 graduation nursing courses. Themes related to stomatherapy are present in mandatory, elective or extension activities. It was identified a predominance of wound content in mandatory subjects, and the themes ostomy and incontinence are offered mainly in elective subjects or extension activities. Conclusion: the research aims to offer the PIHE subsidies for reflection and curriculum evaluation in the dissemination of topics related to stomatherapy in higher education in nursing.